Analisis Eksternalitas Kerajinan Rumah Tangga Cincau Hitam Terhadap Penyerapan Tenaga Kerja Dan Lingkungan di Gampong Jawa Kota Langsa - Riska Lidya Fitra; Yani Rizal; Iskandar Iskandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the externalities of the existence and activities of black grass jelly household crafts on labor absorption and the environment in Gampong Jawa. The study uses primary data obtained from distributing questionnaires. Data collection used a simple random sampling technique with 65 respondents. The model used in this study uses a quantitative descriptive analysis method with results measurement using a Likert scale. The results of the study indicate that the activities of black grass jelly household crafts in Gampong Jawa, Langsa City provide positive externalities on labor absorption with a labor absorption aspect index value of 77.54%. The environmental aspect index value was obtained with a total value of 76.51% which means that it is agreed that the activities of black grass jelly household crafts in Gampong Jawa, Langsa City provide a relatively smaller negative effect/externality, which is only 23.49%.